Memahami Allah Sebagai Sumber Keadilan (Suatu Analisis Konteks Nahum 1:1-8) - Jakarias (Perspektif, 2024)
The focus of this paper is the analysis of the context of the book of Nahum 1:1-8, with the aim of exploring the understanding of the historical, social, and theological background that influenced the writing and message of this book. Which text Nahum 1:1-8 is one of the texts in the Old Testament that prophesies about Nineveh. The analytical method used is a literature study by exploring the Cultural and Social Context of the text, so that readers can understand how Assyrian culture and society play a role in the narrative and how that culture influences their depiction in the book, so that it will appear on the surface that the social impact that occurred in the city of Nineveh was that the city was identified as going to fall. Finally, this analysis finds how this book reflects the views of Israelite society about power and destruction. The relevance of this writing provides insight into the historical and social context of that time, especially regarding the cruelty of the Assyrian empire and the feelings of the oppressed people. This is intended to invite the wise reader to find God in every event in life, especially in times of trouble. Because God pays attention to those who sincerely seek and believe in Him. Readers can learn from the Israelites, how they realized that God is the basis of hope, the guarantor in various difficulties, especially when experiencing injustice.